Erythritol, a Non-Nutritive Sugar Alcohol Sweetener and the Main Component of Truvia®, Is a Palatable Ingested Insecticide - Baudier, Kaitlin M. (Public Library of Science, 2014)
Insecticides have a variety of commercial applications including urban pest control, agricultural use to increase crop yields, and prevention of proliferation of insect-borne diseases. Many pesticides in current use are synthetic molecules such as organochlorine and organophosphate compounds. Some synthetic insecticides suffer drawbacks including high production costs, concern over environmental sustainability, harmful effects on human health, targeting non-intended insect species, and the evolution of resistance among insect populations. Thus, there is a large worldwide need and demand for environmentally safe and effective insecticides. Here we show that Erythritol, a non-nutritive sugar alcohol, was toxic to the fruit fly Drosophila melanogaster. Ingested erythritol decreased fruit fly longevity in a dose-dependent manner, and erythritol was ingested by flies that had free access to control (sucrose) foods in choice and CAFE studies. Erythritol was US FDA approved in 2001 and is used as a food additive in the United States. Our results demonstrate, for the first time, that erythritol may be used as a novel, environmentally sustainable and human safe approach for insect pest control.